Strengthening Maternal Social Support and Promoting Child Dental and Oral Health Through "Bu GISELA” Educational Book - Sosiawan, Agung; Anjani, Nindya Rizqi; Regina, Veronica; Mahiswari, Diyang; Hadinata, Daniel; Wardi, Ully Nafisah; Nugroho, Sepdhyo Wahyu; Ramadhani, Maya Eka; Rumokoi, Rauhansen Bosafino; Sholihah, Nimatus; Afidati, Yasinta Izzah (Indonesian Journal of Dental Medicine, 2020)
Background: Two main influencing factors of dental and oral health in developing countries are attitude and behavior. According to Lawrence Green's theory, a person's behavior is influenced by intention, namely reinforcing factor, predisposing factor, and enabling factor. One of reinforcing factors that has an important role for a mother in adopting and promoting healthy behavior is social support. The study found issues on two social support domains, which were information support and instrumental support. Therefore, "Bu GISELA” or Buku Gigi Sehat Keluarga (Family Dental Health Book) was created to promote dental and oral health by habituating regular tooth-brushing activities. Purpose: To promote dental and oral health care and maternal social support in mothers and kindergarteners in Made Urban Village. Bu GISELA was expected to improve informational support in mothers. Methods: A total of 20 mothers of kindergarteners in Made Urban Village filled pre-test and post-test questionnaires. The obtained data were then processed using a paired t-test to see the relationship between the two variables. Results: A significant increase in knowledge (p-value <0.05) on post-test compared to pre-test. Conclusion: Mothers' dental health knowledge and social support increased significantly after they received "Bu GISELA”.